Associated With Hospitalisation of Hypertensive in-patients in a Tertiary Hospital, Southwestern Nigeria (2023)
The study aimed at estimating the cost of hospitalisation associated with medication non-adherence (MNA) among hypertensive in-patients in a tertiary healthcare facility in southwestern Nigeria. It involved a cross-sectional retrospective review of 322 medical records of hypertensive in-patients at the University College Hospital between 2013 and 2015. Physician’s documentation of MNA in the patients’ medical records prior to admission determined the eligibility into the study. Direct medical costs mainly consultation, medications, laboratory costs for individual patients during hospitalisation were calculated using out-of-pocket payer’s perspective approach. Data were summarised with descriptive statistics, Pearson’s product moment correlation coefficient was used to determine relationship between length of stay in hospital, cost of management and number of comorbidities at p < 0.05 considered statistically significant. Of the 322 medical records of hypertensive in-patients evaluated within the 3-year study period, 230 (71.4%) had a documentation of MNA. The average age was 55.9 ± 15.7 years old. Artisans/self-employed (n = 82; 35.7%) and petty traders (n = 61; 26.5%) made up the majority of the patients. The total cost of hospitalisation for the period studied was USD100,461.40 for all the patients, with an average of USD52.00 ± 28.10/patient/day, more than a quarter of which was spent on pharmaceuticals. Similarly, the costs of management also increased with increase in length of hospitalisation (Pearson’s product moment correlation r = 0.539, p = 0.000). The number of comorbid diseases increased the length of hospitalisation (r = 0.133, p = 0.044). Cost associated with hospitalisation in relation to MNA is high among the studied participants. There is a need to develop strategies to enhance medication adherence among patients with hypertension.